Desenvolvimento de dispositvo IoT para monitoramento da inclinação de contenção em gabião caixa: um exemplo de engenharia 4.0 - Silva, Anderson Bezerra da (2023)
Containment structures are used to promote the stabilization of soil, rock or mixed masses, in order to contain mass movements that can generate landslides, causing environmental and material damage and in some cases injuring people. These structures are an important element of urban infrastructure and are works that require safety and durability. Due to their importance, containments must be periodically inspected to ensure that their structural conditions and the characteristics of the contained massif are compatible with the parameters foreseen in the project. With the advancement of technology, new resources are available for collecting and analyzing structures, both to verify their current condition and to predict their future conditions. In the present work, an electronic device was developed, used and evaluated for monitoring and measuring the inclination of a bank containment structure, executed in box-type gabions. The monitored containment was implemented in the neighborhood of São Mateus, east zone of the city of São Paulo. The equipment responsible for monitoring was an IoT (Internet of Things) device, which collected information from an acceleration sensor and sent it over the internet to a cloud server. Once on the cloud server, these data were stored in a database allowing access to the history of the slope variation. The readings collected by the equipment were exported, via IoT, to an electronic spreadsheet, which made it possible to correlate their variations to the executive phases of containment. Additionally, statistical analyzes were carried out to verify whether the variations captured by the sensor consisted or not of a possible failure of the containment. Carrying out a significant number of readings, monitoring the variation of these readings through a simple access interface, storing them in a database and the possibility of exporting these data to carry out statistical analyzes and customized reports, are among the main benefits of using the IoT device for the monitoring performed.